Gestión de áreas verdes urbanas y bienestar social de los usuarios de la Municipalidad Provincial de Alto Amazonas Yurimaguas 2024 - Rios Muñoz, Clara Katiana (2025)
The present research study aimed to determine the relationship between the management of urban green areas and the social well-being of the users of the Provincial Municipality of Alto Amazonas Yurimaguas 2024. A basic descriptive correlational study was carried out with a non-experimental design. For data collection, the survey technique and the questionnaire were used, taking 383 citizens as the study population, who were essential for the development of the research. The study concluded that the management of green areas in the Municipality of Alto Amazonas, Yurimaguas, is considered regular, with an index of 24%. This situation is due to the sporadic efforts of the municipality to raise awareness among the population about the importance of green areas. Regarding social well-being in said institution, it was also rated as regular, with an index of 25%, since the respondents stated that they do not feel part of their community. Finally, a significant relationship between urban green area management and social well-being is highlighted, with moderate positive correlations of 0.656, 0.609 and 0.585 for management, promotion and treatment respectively, while the complementary measures present a lower positive correlation of 0.478; all are highly significant with a significance level of 0.000.